International validation and update of the Amsterdam model for prediction of survival after pancreatoduodenectomy for pancreatic cancer. Issue 5 (May 2020) - van Roessel, Stijn; Strijker, Marin; Steyerberg, Ewout W.; Groen, Jesse V.; Mieog, J. Sven; Groot, Vincent P.; He, Jin; De Pastena, Matteo; Marchegiani, Giovanni; Bassi, Claudio; Suhool, Amal; Jang, Jin-Young; et al.
Abstract: Background: The objective of this study was to validate and update the Amsterdam prediction model including tumor grade, lymph node ratio, margin status and adjuvant therapy, for prediction of overall survival (OS) after pancreatoduodenectomy for pancreatic cancer. Methods: We included consecutive patients who underwent pancreatoduodenectomy for pancreatic cancer between 2000 and 2017 at 11 tertiary centers in 8 countries (USA, UK, Germany, Italy, Sweden, the Netherlands, Korea, Australia). Model performance for prediction of OS was evaluated by calibration statistics and Uno's C-statistic for discrimination. Validation followed the TRIPOD statement. Results: Overall, 3081 patients (53% male, median age 66 years) were included with a median OS of 24 months, of whom 38% had N2 disease and 77% received adjuvant chemotherapy. Predictions of 3-year OS were fairly similar to observed OS with a calibration slope of 0.72. Statistical updating of the model resulted in an increase of the C-statistic from 0.63 to 0.65 (95% CI 0.64–0.65), ranging from 0.62 to 0.67 across different countries. The area under the curve for the prediction of 3-year OS was 0.71 after updating. Median OS was 36, 25 and 15 months for the low, intermediate and high risk group, respectively (P < 0.001). Conclusions: This large international study validated and updated the Amsterdam model for survival prediction after pancreatoduodenectomy for pancreatic cancer. The model incorporates readily available variables with a fairly accurate model performance and robustness across different countries, while novel markers may be added in the future. The risk groups and web-based calculator www.pancreascalculator.com may facilitate use in daily practice and future trials. Highlights: This study validated and updated the Amsterdam prediction model for patients who underwent pancreatoduodenectomy for pancreatic cancer in an international cohort of 3, 081 patients. The prediction model uses tumor grade, lymph node ratio, margin status and adjuvant therapy to predict 3-year overall survival. Performance was fairly accurate with an AUC for 3-year OS of 0.71 after updating. The web-based calculator is available at www.pancreascalculator.com .